2010
DOI: 10.1590/s0100-06832010000400009
|View full text |Cite
|
Sign up to set email alerts
|

Seeds enriched with phosphorus and molybdenum improve the contribution of biological nitrogen fixation to common bean as estimated by 15n isotope dilution

Abstract: SUMMARYSeeds with a high concentration of P or Mo can improve the growth and N accumulation of the common bean (Phaseolus vulgaris L.), but the effect of enriched seeds on biological N 2 fixation has not been established yet. This study aimed to evaluate the effect of seeds enriched with P and Mo on growth and biological N 2 fixation of the common bean by the 15 N isotope dilution technique. An experiment was carried out in pots in a 2 x 3 x 2 x 2 factorial design in randomized blocks with four replications, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
(52 reference statements)
3
2
0
Order By: Relevance
“…The application of P to bean plants also resulted in decreased shoot δ 15 N values, an indication of higher N 2 fixation (Table 3 ) and this agrees with the findings of Chagas et al ( 2010 ). However, there was a positive synergistic effect of Rhizobium inoculation and P-fertilisation on plant growth and symbiotic performance, as indicated by the lower shoot δ 15 N values, greater %Ndfa, and increased amount of N-fixed in plants treated to P and Rhizobium (Table 3 ).…”
Section: Discussionsupporting
confidence: 91%
“…The application of P to bean plants also resulted in decreased shoot δ 15 N values, an indication of higher N 2 fixation (Table 3 ) and this agrees with the findings of Chagas et al ( 2010 ). However, there was a positive synergistic effect of Rhizobium inoculation and P-fertilisation on plant growth and symbiotic performance, as indicated by the lower shoot δ 15 N values, greater %Ndfa, and increased amount of N-fixed in plants treated to P and Rhizobium (Table 3 ).…”
Section: Discussionsupporting
confidence: 91%
“…This confirmed that N 2 fixation during early pod filling is extremely important for common bean (Kumarasinghe et al, 1992;Kimura et al, 2004). Estimates of contribution of N 2 fixation, assessed by 15 N isotope dilution in bean plants grown in pots with soil of other authors were rather similar: 50 to 72 % (Rondon et al, 2007) or 54 to 79 % (Chagas et al, 2010). Using the 15 N natural abundance method, Mortimer et al (2008) estimated contributions of biological fixation of 50 to 55 % in beans grown in nutrient solution.…”
Section: Nitrogen Metabolismsupporting
confidence: 69%
“…A t-test at 0.05 probability was used to check the similarity of 15 N enrichment among plant parts for each harvest. In the different bean plant parts, 15 N enrichment was similar (Table 1), as verified by Wolyn et al (1991) in the best N 2 -fixing bean lines and by Chagas et al (2010) in a pot experiment. The leaves contained 67 and 40 % of the total N accumulated by inoculated plants 52 and 71 DAE, respectively, averaged across all treatments.…”
Section: Assayssupporting
confidence: 53%
See 1 more Smart Citation
“…It can be inferred that in the soil, which is a complex system, the activity of phosphatases can also be controlled by other factors such as the concentration of substrates of the enzymes, the presence or absence of metals and others. Many elements are important for plant growth (Kevresan et al 2001) and biological nitrogen fixation (Chagas et al 2010) but amounts in excess can inhibit phosphatase acid activity (Huang and Shindo 2000;Tsekova et al 2002, Quiquampoix andMousain 2005). For example, acid phosphatase from Ustilago sp.…”
Section: Introductionmentioning
confidence: 99%